Hsp70 Oligomerization Is Mediated by an Interaction between the Interdomain Linker and the Substrate-Binding Domain - Aprile, Francesco A. (Public Library of Science, 2013)
Oligomerization in the heat shock protein (Hsp) 70 family has been extensively documented both in vitro and in vivo, although the mechanism, the identity of the specific protein regions involved and the physiological relevance of this process are still unclear. We have studied the oligomeric properties of a series of human Hsp70 variants by means of nanoelectrospray ionization mass spectrometry, optical spectroscopy and quantitative size exclusion chromatography. Our results show that Hsp70 oligomerization takes place through a specific interaction between the interdomain linker of one molecule and the substrate-binding domain of a different molecule, generating dimers and higher-order oligomers. We have found that substrate binding shifts the oligomerization equilibrium towards the accumulation of functional monomeric protein, probably by sequestering the helical lid sub-domain needed to stabilize the chaperone: substrate complex. Taken together, these findings suggest a possible role of chaperone oligomerization as a mechanism for regulating the availability of the active monomeric form of the chaperone and for the control of substrate binding and release.